High prevalence of exercise-induced ischemia in the asymptomatic limb of patients with apparently strictly unilateral symptoms and unilateral peripheral artery disease. (January 2019) - Henni, Samir; Bauer, Pascal; Le Meliner, Tanguy; Hersant, Jeanne; Papon, Xavier; Daligault, Mickael; Chretien, Jean-Marie; Ammi, Myriam; Picquet, Jean; Abraham, Pierre
Background: The prevalence of exercise-induced ischemia in the asymptomatic limb of patients with unilateral claudication based on history and treadmill evaluation, and with unilateral ipsilateral peripheral artery disease (i.e ankle-to-brachial systolic pressure index <0.90) is unknown. Methods: We detected exercise-induced ischemia in the asymptomatic limb of patients with apparently unilateral claudication. Among 6059 exercise-oximetry tests performed in 3407 nondiabetic and 961 diabetic patients. We estimated the intensity of ischemia in the both limb (buttocks and calves) using the lowest minimum value of the decrease from rest of oxygen pressure (DROP; limb changes minus chest changes from rest), with significant ischemia defined as DROP lower than −15 mmHg. Results: We found 152 tests performed in 142 nondiabetic patients and 40 tests performed in 38 diabetic patients. The asymptomatic limb showed significant ischemia in 46.7% and 37.5% of the tests. Strictly unilateral exercise-induced claudication with apparently unilateral peripheral artery disease was rare (<4% of all tests). However, among these highly selected tests, significant ischemia was found in the asymptomatic limb in more than one-third of cases. Conclusion: The asymptomatic limb of patients with peripheral artery disease should not be considered a normal limb.